2010
DOI: 10.1577/t09-217.1
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Hurricane Katrina on Freshwater Fish Assemblages in a Small Coastal Tributary of Lake Pontchartrain, Louisiana

Abstract: Hurricane Katrina struck southeastern Louisiana on 29 August 2005 and thereby created an opportunity to examine the effects of a catastrophic storm on fish assemblages in a coastal stream. Bayou Lacombe is a small (46.1 river kilometers), primarily freshwater stream that drains into the northeastern portion of Lake Pontchartrain, a large oligohaline estuary located north of New Orleans. In summer 2005 (prior to the hurricane), three upstream and three downstream reaches of Bayou Lacombe were surveyed by electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The marked decrease in salinity soon after the cyclone due to the heavy and prolonged rain shifted the composition of fish assemblages of the Matla River with higher abundance of freshwater species such as Mystus gulio and Glossogobius giuris. The result corroborated with previous reports (Paperno et al 2006, Vrancken & O'Connell 2010.…”
Section: Pre-ailasupporting
confidence: 93%
“…The marked decrease in salinity soon after the cyclone due to the heavy and prolonged rain shifted the composition of fish assemblages of the Matla River with higher abundance of freshwater species such as Mystus gulio and Glossogobius giuris. The result corroborated with previous reports (Paperno et al 2006, Vrancken & O'Connell 2010.…”
Section: Pre-ailasupporting
confidence: 93%
“…Consequently, large nonstorm related fish kills are typically not experienced during the ARB flood pulse. Conversely, acute hurricane-associated reductions in DO can result in extensive fish mortality (Tabb and Jones 1962;Knott and Martore 1991;Tilmant et al 1994;Mallin et al 1999;Mallin et al 2002;Burkholder et al 2004) and lead to observed changes in fish community abundance and composition (Greenwood et al 2006;Paperno et al 2006;Stevens et al 2006;Van Vrancken and O'Connell 2010). Because of rapid oxygen decline rates (4.32 mg/L/day to hypoxia then 0.48 mg/L/day to near anoxia), we observed near anoxic conditions at all 16 sample stations less than a week (0.23 mg/L mean DO concentration, Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the difficulty in predicting the landfall of a hurricane, researchers often rely on variations in long-term organismal monitoring programs (Stevens et al 2006) or inter-annual changes in biogeochemical cycles (Paerl et al 2001) to assess both temporary and longer-term impacts associated with large-scale storms. Although multiple studies have documented storm-related shifts in the density, distribution, and composition of various aquatic biota, such as benthic macrofauna (Balthis et al 2006;Poirrier et al 2008), decapods (Knott and Martore 1991), fishes (Greenwood et al 2006;Paperno et al 2006;Stevens et al 2006;Van Vrancken and O'Connell 2010), and aquatic plants (Havens et al 2001;James et al 2008;Jin et al 2011), most studies do not have real-time environmental data directly associated with passage of the storm. Further, although considerable research has addressed storm-related impacts on ecosystem-level physical processes such as deleterious nutrient cascades (Paerl et al 2001) and episodic hypoxia events (Stevens et al 2006), most hurricane related studies have chronicled conditions in brackish systems.…”
Section: Introductionmentioning
confidence: 99%
“…Resh et al., 1988), as well as redistributes flora and fauna (e.g. van Vrancken & O'Connell, 2010). While major flow disturbances are well‐studied in stream ecosystems, there are relatively few studies of hurricane impacts on stream communities and even fewer investigations focused on evaluating disturbance effects along an aridity gradient.…”
Section: Introductionmentioning
confidence: 99%